Revegetation technique changes root mycorrhizal colonisation and root fungal communities: the advantage of direct seeding over transplanting tube-stock in riparian ecosystems - Bermúdez-Contreras, Ana I.; Ede, Fiona; Waymouth, Vicky; Miller, Rebecca E.; Aponte, Cristina (Plant ecology, 2020)
Riparian ecosystems are among the most degraded worldwide as they are subject to a range of human-mediated disturbances at different scales. As riparian vegetation plays a key role in maintaining waterway and landscape health, restoration often focuses on promoting riparian vegetation re-establishment. The role of below-ground processes and agents in the process of revegetation is often overlooked even though agents like mycorrhizal fungi enhance seedling establishment and plant growth. In this study we aimed to understand whether colonisation by local mycorrhizal fungi can be advantageous to the early phases of plant establishment during revegetation, whether revegetation technique influences the extent of this potential colonisation, and has the potential to enhance revegetation outcomes. We examined mycorrhizal colonisation rate and species composition of root fungal communities in direct seeded and tube-stock plants and compared them with local native vegetation in a retarding basin in Victoria, Australia, then modelled the relationship between root fungal community attributes and plant size. Results indicate that revegetation technique influenced the colonisation rate, diversity and composition of root fungal communities. Moreover, greater fungal diversity and greater similarity of fungal communities to the mycobiota of native vegetation were positively related with growth of seeded plants but showed negative or little relationship to size of tube-stock plants. High colonisation rates of plant species studied, and relationships between fungal community characteristics and plant growth of seeded plants provide the first evidence of the potential importance of mycorrhizal associations for these plant species in a revegetation context.